2011
DOI: 10.1002/lt.22231
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant depression, antidepressant use, and outcomes of orthotopic liver transplantation

Abstract: Depression is a common problem among patients awaiting organ transplantation, but little is known about the impact of depression and its treatment on the outcomes of liver transplantation. In this retrospective cohort analysis, we studied all patients over 18 years of age who underwent liver transplantation during a 5-year period (2004)(2005)(2006)(2007)(2008) at a single center. Among 179 recipients, 65 patients had depression, as defined by a health care provider assessment, before transplantation. Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 18 publications
3
67
1
1
Order By: Relevance
“…ticipate in a follow-up study between Oct. 1,2001, and Aug. 31, 2004. The 4263 men who attended a face-to-face follow-up survey and the 1322 who completed a follow-up questionnaire constitute the Health in Men Study cohort (n = 5585).…”
Section: Resultsmentioning
confidence: 99%
“…ticipate in a follow-up study between Oct. 1,2001, and Aug. 31, 2004. The 4263 men who attended a face-to-face follow-up survey and the 1322 who completed a follow-up questionnaire constitute the Health in Men Study cohort (n = 5585).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective analysis of patients with end-stage liver disease of different aetiologies who received OLT demonstrated that amongst patients with depression prior to surgery, those taking antidepressants at the time of OLT experienced significantly less acute cellular rejection (13%) than depressed patients not receiving antidepressants (40%). 10 The group hypothesised that effective treatment of depression was associated with increased compliance with immunosuppressant medications. No difference in time to death or incidence of graft dysfunction was observed between depressed and nondepressed groups, consistent with other studies that have also failed to show that pre-operative depression per se is a risk factor for poor post-OLT outcome.…”
Section: Depression In Patients With Chronic Liver Disease Cirrhosismentioning
confidence: 99%
“…A study in which domains of anxiety and depression were combined, reported a diagnosis of adjustment disorder or depression in upto 36% of the patients awaiting liver transplantation. 44 Personality characteristics and coping abilities have been evaluated in patients waiting to undergo liver transplant. It has been seen that patients frequently have maladaptive coping styles with poor fighting spirit, anxious preoccupations, hopelessness, negation and fatalism being found frequently.…”
mentioning
confidence: 99%